Smart transportation systems 2021 proceedings of 4th KES-STS International Symposium - Qu, Xiaobo; Zhen, Lu; Howlett, Robert J.; Jain, Lakhmi C. (Smart innovation, systems, and technologies, 2021)
This book gathers selected papers presented at the KES International Symposium on Smart Transportation Systems (KES-STS 2021). Modern transportation systems have undergone a rapid transformation in recent years, producing a range of technological innovations such as connected vehicles, self-driving cars, electric vehicles, Hyperloop, and even flying cars, and with them, fundamental changes in transport systems around the world. The book discusses current challenges, innovations, and breakthroughs in smart transportation systems, as well as transport infrastructure modelling, safety analysis, freeway operations, intersection analysis, and other related cutting-edge topics.